Ganymede's gravity, tides and rotational state from JUICE's 3GM experiment simulation. (August 2020) - Cappuccio, P.; Hickey, A.; Durante, D.; Di Benedetto, M.; Iess, L.; De Marchi, F.; Plainaki, C.; Milillo, A.; Mura, A.
Abstract: The JUpiter Icy Moons Explorer (JUICE) is a European Space Agency (ESA) mission that will launch in 2022 and arrive in the Jovian system in 2029 to investigate Jupiter's icy satellites. The mission will perform flybys of the icy moons Europa, Callisto and Ganymede before being inserted into a 280-day orbit around Ganymede: 150 days in Elliptical Orbit (GEO) followed by 130 days Circular Orbit at 500 km (GCO-500). During the orbital phase, JUICE will investigate the moon's surface, interior and exosphere, carrying out for the first time a complete characterization of an icy satellite. A suite of field and particle instruments will characterize the plasma and magnetic environment around the body. The 3GM experiment on board the spacecraft will exploit the GCO-500 phase to collect accurate Doppler and range measurements to determine the moon's orbit, gravity field and tide, therefore providing crucial information to accurately model its internal structure. The simulations carried out reveal that the moon's gravity field can be determined up to degree and order 40, depending on the magnitude of the gravity spectrum. The Love number k 2, modelling the gravitational response to eccentricity-driven, time-variable gravity gradient from Jupiter, is determined with an accuracy of σ k 2 ∼ 10 − 4 . The obliquity, φ, and the libration at orbital period, ϕ, can be retrieved with a level of uncertainty of 1 and 2 μ r a d, respectively. Because of the 97 m 2 solar panels and the ensuing large area-to-mass ratio, JUICE will be affected by neutral particle drag. Here, we also assess the potential effect of spacecraft drag due to Ganymede's tenuous exosphere, which ranges between 10 − 17 − 10 − 16 k g / m 3 and generates an average drag of ∼ 4 ⋅ 10 − 12 m / s 2, in the GCO-500 phase.